2014
DOI: 10.2134/jeq2014.03.0099
|View full text |Cite
|
Sign up to set email alerts
|

Safety of Gardening on Lead- and Arsenic-Contaminated Urban Brownfields

Abstract: Elevated levels of lead (Pb) and arsenic (As) are not uncommon for urban soils. Test plots were established at urban gardens in Tacoma and Seattle, WA. The Tacoma site was contaminated with Pb (51-312 mg kg) and As (39-146 mg kg), and the Seattle site had high Pb soil concentrations ranging from 506 to 2022 mg kg and As concentrations of <20 mg kg. The efficacy of biosolids mix and compost amendment in reducing Pb and As concentrations in three vegetables (carrots, lettuce, and tomatoes) and the bioaccessibili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(51 citation statements)
references
References 72 publications
3
48
0
Order By: Relevance
“…Consistent with previous research [31,32], plant TF data indicated that the garden plants in this study tended to concentrate As from soils in tissues more heavily than Pb across the range of observed soil As and Pb concentrations, with As TFs averaging 0.105 compared to an average Pb TF of 0.056. The higher concentrations of Pb than As in plant tissues observed in this study, therefore, were likely a result of the higher total Pb concentrations in the garden soils as compared to As, averaging 30.3 and 6.9 mg/kg for soil Pb and As respectively.…”
Section: Discussionsupporting
confidence: 90%
“…Consistent with previous research [31,32], plant TF data indicated that the garden plants in this study tended to concentrate As from soils in tissues more heavily than Pb across the range of observed soil As and Pb concentrations, with As TFs averaging 0.105 compared to an average Pb TF of 0.056. The higher concentrations of Pb than As in plant tissues observed in this study, therefore, were likely a result of the higher total Pb concentrations in the garden soils as compared to As, averaging 30.3 and 6.9 mg/kg for soil Pb and As respectively.…”
Section: Discussionsupporting
confidence: 90%
“…These thresholds are likely to be site-specific because of the effect that local soil properties and contaminant source have on plant availability of Pb and As. For example, two recent studies (Attanayake et al 2015, Defoe et al 2014) showed very limited As uptake into root crops and leafy vegetables, even though soil total arsenic concentrations at study sites were as high as 95 and 146 mg kg −1 . Arsenic contamination from lead arsenate pesticides may represent a higher level of bioavailability than forms of As from some other contaminant sources (e.g., certain brownfield sites).…”
Section: Resultsmentioning
confidence: 88%
“…The commutability of reference materials to anticipated samples is critical in decreasing measurement uncertainty. This study was focused on soils with heavy metal (primarily Pb) concentrations similar in magnitude to previous urban geochemistry and urban agriculture studies (Finster et al 2004, Clark et al 2006, 2008, Defoe et al 2014, Hu et al 2014, McBride et al 2014, Sharma et al 2015. Therefore, five commercially available NIST soil reference materials encompassing a continuum in heavy metal concentrations, organic carbon and mineralogy likely to be found in urban soils were selected for characterisation.…”
Section: Methodsmentioning
confidence: 99%